Perancangan Aplikasi Monitoring Jaringan Berbasis Web Di PT. Trinitas Mulia Abadi - Yuda Pratama (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The rapid development of network technology in the current era has led to its extensive use in various agencies. The operational stability of network infrastructure is crucial in supporting advances in information technology. Effective computer network monitoring is a major concern for network administrators to ensure network performance remains stable and disturbances can be detected immediately. Losses arising from network operational problems can be significant, especially for agencies that depend on the network. Trinitas Mulia Abadi, a garment company that relies on computer networks for its operations, faces a similar challenge. They need a network monitoring application that can be accessed easily and provides information quickly if there is a problem with the network. This will enable network administrators to monitor network activity for which they are responsible. In order to overcome these problems, designing a network monitoring application that is responsive and easily accessible anywhere is very important. This application will help PT. Trinitas Mulia Abadi in monitoring their network performance efficiently and mitigating the negative impact of potential network operational issues.